Porphyrin-based nanotechnology: a minimally invasive approach for drug delivery and cholesteatoma treatment - Mahmoud, Dina Ashraf; Ding, Lili; Ferdous, Zannatul; Zhang, Zhifen; Chen, Juan; Spiegel, Jennifer L.; Sykes, Edward Alexander; Harrison, Robert; Zheng, Gang; Le, Trung (Frontiers in Surgery, 2025)
The treatment of inner and middle ear diseases remains a significant challenge, often requiring surgical intervention as the only option. In this study, we investigated porphysomes, self-assembled porphyrin-based nanoparticles, as a minimally invasive drug delivery platform for inner ear applications and as photothermal agents for cholesteatoma ablation. Three porphysome formulations were evaluated: parent porphysomes (PS), porphyrin-stabilized nanoemulsions (nPS), and EDTA-lipid incorporated porphysomes (ePS). Rats received intratympanic injections of each formulation, and fluorescence imaging performed 1 h postinjection demonstrated concentration-dependent inner ear penetration for all formulations. Notably, no signs of ototoxicity were observed based on histological and functional assessments of hearing and balance. Among ePS-treated rats, the 250 and 1,000 μM groups showed significantly higher inner ear fluorescence compared with the 50 μM group. Auditory brainstem response (ABR) and distortion product otoacoustic emission (DPOAE) tests were performed at baseline and 2 and 6 weeks postinjection. No significant threshold shifts were detected in PS and ePS groups compared with controls. In contrast, nPS-treated rats exhibited a significant ABR threshold elevation at 6 weeks (p < 0.02). At 6 weeks, minor yet statistically significant DPOAE threshold differences were observed at 16 kHz (PS group) and 32 kHz (all porphysome groups); however, all shifts remained below 0 dB, indicating no functional hearing loss. Vestibular assessments, including swim and beam tests, revealed no significant impairments. Upon laser activation, all porphysome formulations induced substantial temperature elevation (ΔT = 31 ± 3.76°C, p < 0.05) and histological burn effects in cholesteatoma tissues. These findings support the potential of porphysomes as a safe, minimally invasive drug delivery system and photothermal agent for the treatment of inner and middle ear disorders.